EFFECT OF SPLITTER VANES ON BLOWER PERFORMANCE - R, Sabareesh; Karuppusami, Dr.G.; Mascomani, Mr.R. (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
A Centrifugal air blower is a mechanical device which uses centrifugal force to propel air forward. Inside a centrifugal air blower is a wheel with small blades on the circumference and a casing to direct the flow of air into the center of the wheel and towards the edge. Splitter vanes are additional, smaller airfoils that are placed circumferentially between the main blades of the rotor to improve overall performance in terms of velocity and pressure distribution. The diffusion of flow process is highly complex in blower operation which affects the performance of the blower. The performance of the blower can be enhanced by introducing splitter vanes at judiciously selected locations with optimized parameters. This project aims at studying the effect of splitter vanes on the performance of the blower and redesigning the existing blower with splitter vanes. The modified blower is then analyzed using CFD and the results are compared with the existing blower.